On the meeting of Nicholas I with local residents during the trip to the Caucasus (1837) in the documents and works of pre-revolutionary authors - Zuleikha Zh. Glasheva (Кавказология)
The article examines the Emperor’s Nicholas I of Russia travels through the Caucasus in a difficult situation.. By the end of the 30-s XIX century, the need for radical transformations in politics in the Caucasus was realized not only by local officials but also by St. Petersburg. The emperor planned a trip to become acquainted with the state of events in the Caucasus. With Nicholas I’s tour across the Caucasus, hopes for the conclusion of the Caucasian War and the region’s final “peace” were intertwined. There was no unity in the mountain community; one faction favored reconciliation, while the other supported the continuation of military opposition to the Russian Empire’s growth in the region. The purpose of the trip was to get to know the highlanders and negotiate with them. The highlanders presented to the emperor were in the category of “peaceful,” many of them had military ranks, some went through Amanatstvo. Most of the deputies contacted the military or civil administration in the Caucasus, had ideas about Russian culture.The list of deputies identified in the Russian Military Historical Archive and delivered to the Emperor in Vladikavkaz, Stavropol, and Yekaterinodar is included in the appendix. These lists are of significant scholarly relevance because they allow us to declare with certainty that by the end of the nineteenth century, the Caucasian administration had inspected the ethnic composition of the North Caucasian peoples. The documents in the appendix have been published while retaining the original’s stylistic and archaeographic qualities.